Cognitive Effects of Phenobarbital - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Neurocognitive behavior in 9 children with various epilepsies was evaluated before and at 6 months after discontinuing phenobarbital monotherapy at the Department of Child Neurology, Instituto Nazionale Neurologico "Carlo Besta;" Milano, Italy.